The Strategy for Absolute Poverty Alleviation in Pasuruan Regency - Wismanu, Rendra Eko; Humam, Muhammad Iqbal; Rizky, Achmad Reza (Universitas Tribhuwana Tunggadewi, 2024)
Poverty is a complex and multidimensional problem and has become a global, national, and even local issue, so it needs to be a priority for development. Poverty not only describes economic powerlessness but is also related to the ability to fulfill people's fundamental rights. Therefore, poverty is a phenomenal problem in all aspects, requiring attention and making every effort to resolve the problem of poverty by carrying out medium- and short-term planning in the context of reducing poverty rates and alleviating extreme poverty. Various strategies have been attempted to reduce the poverty rate, including the central government's commitment, demonstrated by setting a target of eliminating extreme poverty by 2024 to reach 0%, which must be carried out in a consolidated, integrated, and targeted manner. The performance of poverty management in Pasuruan Regency has a positive trend of decreasing. In 2022, poverty will be 8.96%, still below the East Java Province and national average. Pasuruan Regency is one of the districts in East Java Province, and it is a pilot project for handling and eliminating extreme poverty. According to data from the Central Statistics Agency, in 2022, the percentage of the extremely poor in Pasuruan Regency was 1.56% or equivalent to 25,790 people. Kemiskinan merupakan masalah yang kompleks dan bersifat multidimensi serta menjadi isu global, nasional bahkan lokal sehingga perlu menjadi prioritas pembangunan. Kemiskinan tidak hanya menggambarkan ketidak berdayaan ekonomi, tetapi juga berkaitan dengan kemampuan dalam memenuhi hak-hak dasar masyarakat. Oleh karena itu Kemiskinan sebagai persoalan fenomenal dalam segala aspek, memerlukan perhatian dan mengusahakan segala upaya untuk menyelesaikan persoalan kemiskinan dengan melakukan perencanaan jangka menengah maupun jangka pendek dalam rangka penurunan angka kemiskinan dan pengentasan kemiskinan ekstrim. Berbagai strategi telah diupayakan untuk menurunkan angka kemiskinan termasuk komitmen pemerintah pusat ditunjukkan dengan penetapan target penghapusan kemiskinan ekstrem pada 2024 mencapai 0% yang harus dilakukan secara terkonsolidasi, terintegrasi dan tepat sasaran. Kinerja penanganan kemiskinan di Kabupaten Pasuruan trendnya positif mengalami penurunan. Pada tahun 2022 Kemiskinan berada diangka 8,96% dan masih berada di bawah rata-rata Provinsi Jawa Timur maupun nasional. Kabupaten Pasuruan merupakan salah satu kabupaten di Provinsi Jawa Timur yang menjadi pilot project penanganan dan penghapusan kemiskinan ekstrim. Merujuk pada data Badan Pusat Statistik, pada tahun 2022 persentase penduduk miskin ekstrim di Kabupaten Pasuruan adalah 1,56% atau setara dengan 25.790 jiwa